DIGITALISASI PEMBERDAYAAN EKONOMI GUNA MENGAKSELERASI PRODUKTIVITAS DAN STABILITAS UMKM DESA TASIKREJO KEC. ULUJAMI KAB. PEMALANG - Pratomo Cahyo Kurniawan; Rohmad Abidin; Syifa Rohmah (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
UMKM as drivers of the populist economy which are the backbone of the Indonesian economy receive special attention from the government to remain protected in order to survive in the midst of the Covid-19 storm. As a result of the prolonged Covid-19 pandemic, companies have suffered losses but many companies are also able to survive by utilizing technology information, especially the use of websites to increase branding and sales of their products/services. The method used in community service activities is to provide E-Marketing training to UMKM actors, most of whom still market their products in the traditional way. Activities in the implementation of community service include: providing counseling as well as training on how to increase sales turnover using digital strategies because currently the community and most consumers of UMKM actors must limit themselves not to interact much with other people. As a result of service activities, participants have an understanding of strategies to survive during a pandemic by utilizing e-marketing such as the introduction of Facebook & Instagram ads and marketplaces